Comparison of indirubin concentrations in indigo naturalis ointment for psoriasis treatment: a randomized, double‐blind, dosage‐controlled trial. (14th December 2017) - Lin, Y.‐K.; See, L.‐C.; Huang, Y.‐H.; Chi, C.‐C.; Hui, R.C.‐Y.
Summary: Background: Indigo naturalis and its refined formulation, Lindioil, are effective in treating psoriatic symptoms topically. Indirubin is the active ingredient in indigo naturalis. Objectives: To determine the efficacy and safety of different concentrations of indirubin in Lindioil ointment for treating psoriasis. Methods: In this randomized, double‐blind trial, adult patients presenting with chronic plaque psoriasis for > 1 year and with < 20% of the body surface area (BSA) affected were randomized to apply Lindioil ointment containing 200, 100, 50 or 10 μg g −1 of indirubin twice daily for 8 weeks followed by an additional 12‐week safety/extension period. The primary end point was the mean percentage change in Psoriasis Area and Severity Index (PASI) score along with the proportion of participants achieving 75% and 90% reductions in PASI scores (PASI 75 and PASI 90, respectively) from baseline to week 8. Results: The results from week 8 revealed that the 200 μg g −1 group had the greatest reduction in PASI score [69·2%, 95% confidence interval (CI) 55·5–82·8], followed by the 100 μg g −1 group (63·1%, 95% CI 52·8–73·5), the 10 μg g −1 group (53·4%, 95% CI 42·8–64·0) and the 50 μg g −1 group (50·3%, 95% CI 37·4–63·2), with a between‐group comparison of P = 0·0445. The group with the highest proportion of the patients achieving PASI 75 (57%, P = 0·0474) and PASI 90 (30%, P = 0·0098) was the 200 μg g −1 group. No severe treatment‐related adverse events were reported during the 20‐week evaluation. Conclusions: An amount of 200 μg g −1 of indirubin in Lindioil ointment is the most effective concentration studied so far for treating psoriasis topically, and is safe. Abstract : What's already known about this topic? As a result of safety concerns about the long‐term use of corticosteroids and other standard treatments, there is a growing demand for herbal treatments for psoriasis. Indigo naturalis, a herb used in Chinese medicine, is effective for the topical treatment of psoriasis when used as a crude ointment or in its refined form, Lindioil. What does this study add? Indirubin is the active ingredient in indigo naturalis, and different concentrations of indirubin in indigo naturalis ointment yield different results in treating psoriasis. This study provides evidence that 200 μg g −1 of indirubin, the highest concentration studied so far, is the most effective concentration and is safe. Linked Comment:  Sekhon and Koo. Br J Dermatol 2018; 178 :21 . Plain language summary available online Respond to this article